Attitude, Perception, and Knowledge of COVID-19 Among General Public in Pakistan - Mahmood, Sammina; Hussain, Tariq; Mahmood, Faiq; Ahmad, Mehmood; Majeed, Arfa; Beg, Bilal Mahmood; Areej, Sadaf (Frontiers in Public Health, 2020)
The World Health Organization has acknowledged coronavirus disease 2019 (COVID-19) disease as a pandemic. Efforts are being made all over the world to raise awareness to prevent the spread of the disease. The goal of this study was to assess the attitude, perception, and knowledge of Pakistani people toward COVID-19 disease. We conducted a cross-sectional survey in which a questionnaire of 17 questions was transformed online on Google forms and was sent to random individuals online. A total of 1,000 questionnaires from individuals throughout Pakistan were evaluated. The results revealed that 42.9% of the participants knew about COVID-19 through social media, the largest source of information. Most of the participants (48.3%) started working from home amid the lockdown; 39.9% of the participants reported that they wash their hands every hour, and 56.9% participants are using a surgical mask. About thermal scanners, 30.5% of the people answered they may be effective, and 46.0% of the people think COVID-19 is a bioweapon; 59% of the participants think everyone is susceptible, whereas 83.9% of the people recognize fever as a primary symptom; 65.2% of the people are practicing social distancing, whereas 85.1% of the people think social gatherings causes spread of the disease. In general, participants had a good knowledge about the disease and a positive attitude toward protective measures. The effective measures are being taken by the government and the public; still, there remains a need for further awareness campaigns and knowledge of safe interventions to combat the spread of disease.